Child's age at parental death and university education - Kailaheimo-Lönnqvist S; Erola J (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Losing a parent due to premature death is generally associated with negative child outcomes. However, the study of possible (modifying) effects of the child's age and family background has been neglected in previous research. In this paper, we analyse the relationship between the child's age at parental death and the child's university education, and we study whether the possible association is modified by the child's family background. We apply ordinary least square regression and linear sibling fixed effect models to high-quality Finnish Census Panel data, consisting of 88,727 children born between 1982 and 1990. According to our results, the negative influence of parental death varies by the child's age; the consequences of parental death for young children were the most adverse. Interestingly, the influence of parental death seemed not to vary by family background.